Digital Ethics from the Perspective of Islamic Education: A Conceptual Study of the Manners of Interacting in Cyberspace - Muhammad Faisal Reza; Novianto Ade Wahyudi; Muhammad Jembar Risky; Abul Mafaakhir (Penerbit Hellow Pustaka, 2025)
This study aims to describe the concept of digital ethics from an Islamic educational perspective, explain the etiquette of interacting in cyberspace based on Islamic values, and analyze the relevance of digital ethics in shaping the character of Muslims with noble morals in the digital age. This study uses a qualitative method with a library research approach sourced from the Qur'an, hadith, classical and contemporary literature, as well as academic articles related to digital ethics and Islamic education. The results of the study show that digital ethics in Islam are based on the values of manners and morals that emphasize the importance of honesty, trustworthiness, responsibility, and politeness in the use of technology and online communication. These ethics serve as moral guidelines for Muslims to avoid negative behaviors such as spreading hoaxes, hate speech, and privacy violations. In addition, Islamic education has a strategic role in shaping students' ethical character through the integration of Islamic values into the curriculum and digital learning practices. Thus, the application of digital ethics based on Islamic values can create a generation of Muslims who are noble, wise in using media, and responsible in utilizing technology as a means of da'wah and for the benefit of the ummah.